Estilo de liderazgo y su influencia en la satisfacción laboral de los colaboradores del Cineplanet Real Plaza - Trujillo 2015. - Castillo Espinoza, Juan Emilio (2016)
Job satisfaction of employees is influenced by different styles of leadership that can coexist in the companies which can have an impact on the work, so this research was aimed to determine the relationship between the styles of leadership and job satisfaction of employees of the Cine Planet Real Plaza Trujillo. We worked with a sample of 33 employees and managers of a total population of 66 that was applied a survey to identify leadership styles prevailing in the company and measure job satisfaction of employees and finally to correlate variables mentioned above; the survey consists of three parts between general data, assessment of leadership styles and the job satisfaction of employees. Concluding that the predominant leadership style is the Transformational; overall job satisfaction of staff is half, while taking into consideration that extrinsic factors the items relating to the hours of work and remuneration have shown a satisfaction low and that there is a high correlation between leadership and job satisfaction of employees of the Cineplanet Real Plaza de Trujillo